Carceral Afterlives : Prisons, Detention, and Punishment in Postcolonial Uganda - Bruce-Lockhart, Katherine, 1990- (Book collections on Project MUSE., 2022)
"This social and political history analyzes how incarceration, a practice and policy with colonial origins, was central to both the exertion of and challenges to state power in postcolonial Uganda. The book also illustrates the persistent imbrication of prisons, punishment, politics, and struggles for decolonization and freedom across the globe"--